2002
DOI: 10.1038/sj.bdj.4801545
|View full text |Cite
|
Sign up to set email alerts
|

A pilot investigation of operator variability during intra-oral light curing

Abstract: Objective To test the hypothesis that operator experience influences the efficacy of light curing in a typical posterior intra-oral location. To investigate whether short cure cycles affect performance. Design A cross-sectional single-centre study designed to assess the efficacy of experienced and inexperienced operators when undertaking simulated intra-oral curing. Setting An in vitro laboratory based investigation conducted in a dental school during 2001. Materials and methods A computer-based technique was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…34 Whilst light activated materials may yield optimal mechanical properties when tested following high levels of radiant exposure as is routine in laboratory based tests this ideal is frequently not met in clinical practice. Studies have shown that there is a high degree of variability between individual operators when performing light curing intraorally 16,17 and as confirmed by the current work. Price et al 17 found that radiant exposure delivered over a 10 s exposure using optimally performing light units ranged between 2.6 4 J/cm 2 and 20.4 J/cm 2 depending on light source and cavity location.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…34 Whilst light activated materials may yield optimal mechanical properties when tested following high levels of radiant exposure as is routine in laboratory based tests this ideal is frequently not met in clinical practice. Studies have shown that there is a high degree of variability between individual operators when performing light curing intraorally 16,17 and as confirmed by the current work. Price et al 17 found that radiant exposure delivered over a 10 s exposure using optimally performing light units ranged between 2.6 4 J/cm 2 and 20.4 J/cm 2 depending on light source and cavity location.…”
Section: Discussionsupporting
confidence: 84%
“…There is up to a tenfold difference in the ability of different operators to deliver adequate radiant exposure even with the same light source. 16,17 A recent clinical simulation study assessed the ability of 20 operators to deliver energy to 2 posterior cavity locations in a mannequin head. 17 The energy delivered by the operators from the high power LED units ranged from 2.6 J/cm 2 to 20.4 J/cm 2 .…”
mentioning
confidence: 99%
“…The advantages for dentists are full control of the beginning of restoration and therefore unlimited work time. However, the convenience of light cure is accompanied by the risk of compromised light delivery when the restoration site is less accessible, for instance, in posterior teeth, deep cavity, and endodontic preparations (Shortall et al 2002). Inadequate light cure leads to poor polymerization, which can cause myriad problems, including reduced bond strength, microleakage, toxicity, and postoperative sensitivity (Baek et al 2008;Goldberg 2008;Federlin and Price 2013;Leprince et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The operator's variability can influence different clinical procedures including the diagnostic process. [ 41 ] In this study, clinicians with a great variety of clinical experience are involved. Dental students are taught a wide range of diagnostic techniques for caries detection, and for caries removal end point assessment, special focus is placed on the latest minimal invasive techniques on a theoretical level; however, their application in the dental school clinical practice is still limited.…”
Section: Discussionmentioning
confidence: 99%